2010
DOI: 10.4049/jimmunol.1000739
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Ancestral Polarity Regulator Protein Kinase Cζ at the Immunological Synapse Drives Polarization of Th Cell Secretory Machinery toward APCs

Abstract: A key feature in T lymphocyte biology is that Th cells rapidly polarize their secretory machinery toward cognate APCs. The molecular mechanisms of these dynamic Th cell responses and their impact on APC biology remain to be elucidated. In this study, we demonstrate that protein kinase Cζ (PKCζ) is rapidly activated at the immunological synapse (IS) in human Th cells interacting with cognate dendritic cells (DCs) and that a functional PKCζ is required for the polarization of Th cell secretory machinery toward D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 37 publications
8
69
0
1
Order By: Relevance
“…S2C), p-PKCζ staining was increased at the IS where it paralleled phospho-tyrosine (p-Tyr) staining. These results indicated that in CTLs, similarly to T H cells (14), the PKCζ pathway is active at the IS. We thus treated CTLs with a selective pseudosubstrate inhibitor of PKCζ (PKCζ-PS) (16) to investigate the impact of PKCζ signaling blockade on MTOC polarization.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…S2C), p-PKCζ staining was increased at the IS where it paralleled phospho-tyrosine (p-Tyr) staining. These results indicated that in CTLs, similarly to T H cells (14), the PKCζ pathway is active at the IS. We thus treated CTLs with a selective pseudosubstrate inhibitor of PKCζ (PKCζ-PS) (16) to investigate the impact of PKCζ signaling blockade on MTOC polarization.…”
Section: Resultsmentioning
confidence: 53%
“…We also provide further evidence that lytic granule secretion might be, under certain circumstances, uncoupled from MTOC dynamics by blocking MTOC polarization with a selective inhibitor of the ancestral polarity protein PKCζ (14,15). Our results show that in conditions in which MTOC polarization is inhibited, no major effect on cytotoxicity and on the activation of caspase-3 in target cells could be detected.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Our results strongly suggest that L-plastin regulates lymphocyte polarity and migration by enabling cells to establish an axis of asymmetry in response to chemokine signaling, in particular, the localization of the F-actin cytoskeleton to the leading edge of the cell. We also uncovered a novel mechanistic link between PKC z, an established regulator of lymphocyte polarity (40)(41)(42)(43), and L-plastin in human T lymphocytes, specifically via PKC z-mediated phosphorylation of L-plastin on its Ser 5 residue. L-plastin expression also influenced the Rac1 activation cycle, Akt phosphorylation, and migration on the integrin ligand ICAM-1, but in a manner that was independent of LFA-1 activation or adhesion.…”
Section: Discussionmentioning
confidence: 99%